Patterns of shell utilization in Petrochirus diogenes (Decapoda, Anomura, Diogenidae) in the Ubatuba region, Sao Paulo, Brazil - Bertini, Giovana (2000)
The objective of this study is to investigate the patterns of shell utilization in Petrochirus diogenes in the Ubatuba region, SP, Brazil. Hermit crabs were obtained from 1993 to 1996 with the aid of a shrimp fishery boat equipped with two double-rigged trawling nets. Shells were identified and weighed, and their maximum aperture width was measured. Hermit crabs were weighed, and their shield length was recorded. A total of 634 P. diogenes specimens, occupying shells of 12 gastropod species, was obtained. The shells of Tonna galea, Zidona dufresnei and Strombus pugilis were the most frequently occupied, the first marked by its larger aperture width and lower average weight. Small hermit crabs inhabited a wide variety of gastropod shells due to their higher availability. However, the utilization of T. galea shells became predominant as the crabs attained larger sizes. Differences in weight and aperture width are known to encourage certain shell utilization patterns and may affect growth and reproduction of hermit crabs.